The biopolitics of Artic tourism development and sustainability - Lunden, Aapo (Via Tourism Review, 2022)
In recent years, the concept of Arctification has been used to describe how spatial simplifications and strategic essentialisation of Northern Europe have been used for branding in tourism. This article deconstructs the Arctification phenomenon into three main dimensions, (I) exogenous tourism development, (II) territorialisation, and (III) consumptive ethics of planetary care. The article claims, from a biopolitical perspective, that arctified visions of tourism and sustainable tourism in the Arctic can be understood as the production of heterotopic spaces. By engaging with Foucault’s concept of heterotopia as spaces of exception based on deviation (alterity) and compensation (sustainability), the article further claims that it provides a valuable framework for analysing contemporary challenges and paradoxes of sustainability and tourism growth strategies in the Arctic. The article illustrates its main arguments by drawing examples of Arctification from Finnish Lapland.